Identification of Candidate Genes Regulating the Seed Coat Color Trait in Sesame (Sesamum indicum L.) Using an Integrated Approach of QTL Mapping and Transcriptome Analysis - Li, Chun; Duan, Yinghui; Miao, Hongmei; Ju, Ming; Wei, Libin; Zhang, Haiyang (Frontiers in Genetics, 2021)
Seed coat color is an important seed quality trait in sesame. However, the genetic mechanism of seed coat color variation remains elusive in sesame. We conducted QTL mapping of the seed coat color trait in sesame using an F2 mapping population. With the aid of the newly constructed super-dense genetic linkage map that comprised of 22,375 bins distributed in 13 linkage groups (LGs), 17 QTLs of the three indexes (i.e., L, a, and b values) of seed coat color were detected in seven intervals on four LGs, with a phenotype variance explanation rate of 4.46% - 41.53%. A new QTL qSCa6.1 on LG 6 and a QTL hotspot containing at least four QTLs on LG 9 were further identified. Variants screening of the target intervals showed that there were 84 genes possessed the variants that were high-impact and co-segregating with the seed coat color trait. Meanwhile, we performed the transcriptome comparison of the developing seeds of a white- and a black-seeded variety, and found that the differentially expressed genes (DEGs) were significantly enriched in 37 pathways, including three pigment biosynthesis related pathways. Integration of variants screening and transcriptome comparison results suggested that 28 candidate genes probably participated in the regulation of the seed coat color in sesame, of which ten genes had been proved or suggested to involve in pigments biosynthesis or accumulation during seed formation. The findings give the basis for mechanism of seed coat color regulation in sesame, and exhibit the effects of the integrated approach of genome re-sequencing and transcriptome analysis on the genetics analysis of the complex traits.